Pengembangan Lembar Aktivitas Matematika Berorientasi Pendekatan Saintifik - Indriani, Novia; Pamungkas, Aan Subhan; Alamsyah, Trian Pamungkas (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research aims to develop mathematics student activity sheets on cube and rectangle box volume material, to determine the quality of mathematicsl activity sheets developed and to find out the user's response to mathematics activity sheets, and to understand students' understanding after using a sheet of mathematics activity. The development research method used in this study refers to the research design of the 4D model developed by Thiagarajan which consists of 4 stages of development namely Define, Design, Develop, and Disseminate. The subjects of this study were 30 fifth grade students at Panancangan Elementary School 2. The results of the study were (1) the average level of feasibility of the mathematics activity sheet reached 84.6% which was included in the category of